Phenotypic differences based on staging of Alzheimer's neuropathology in autopsy-confirmed dementia with Lewy bodies. (October 2016) - Peavy, Guerry M.; Edland, Steven D.; Toole, Belinda M.; Hansen, Lawrence A.; Galasko, Douglas R.; Mayo, Ann M.
Abstract: Introduction: The goal was to compare subgroups of dementia with Lewy Bodies (DLB) using neuropathological measures to differentiate 'pure' Lewy body (LB) dementia from 'mixed' DLB [co-occurring LB and Alzheimer's disease (AD) pathology] to facilitate diagnostic decision-making and future development of interventions based on predicted type(s) of neuropathology. Studies comparing these groups are rare relative to those differentiating 'pure' AD and all-cause DLB, and are limited by insufficient sample size, brief cognitive batteries, and/or absence of autopsy confirmation. To address these limitations, we assessed cognition and other features in a large, autopsy-confirmed DLB sample using an extensive neuropsychological battery. Methods: Subjects from an AD research center autopsy series satisfying DLB pathology criteria were divided by an AD neuropathology index into DLB-LB (Braak stage 0–3) (n = 38) and DLB-AD (Braak stage 4–6) (n = 41) and compared on baseline variables from chart reviews and standardized measures. Results: DLB-LB subjects were more impaired on visuospatial constructions, visual conceptual reasoning, and speed of processing, but less impaired on verbal memory and confrontation naming. All-type hallucinations occurred more frequently in DLB-LB, while delusions were common in both groups. Groups were similar in education and age at onset, and in baseline age, dementia severity, and functional capacity. Conclusion: Salient findings included greater impairment on visual tasks and speed of processing and more frequent reports of all-type hallucinations in DLB-LB compared to DLB-AD. Relatively intact confrontation naming in DLB-LB and no differences in reported delusions were of note. Identifying differences in phenotypic features can improve prediction of underlying neuropathology. Highlights: Autopsy, large sample, and multiple measures improve study of DLB subgroups. Pure DLB results in fewer deficits on confrontation naming and memory than mixed. Pure DLB results in greater deficits on visuospatial and timed tasks than mixed DLB. All-type hallucinations occur more in pure DLB than mixed; delusions common in both. Discerning DLB phenotypic variability is vital for forming effective interventions.